2017
DOI: 10.1177/0271678x17690537
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of microglia in cortical spreading depression in neurological disease

Abstract: Microglia play a pivotal role in innate immunity in the brain. During development, they mature from myeloerythroid progenitor cells in the yolk sac and colonize the brain to establish a resident population of tissue macrophages. In the postnatal brain, they exert phagocytosis and induce inflammatory response against invading pathogens. Microglia also act as guardians of brain homeostasis by surveying the microenvironment using motile processes. Cortical spreading depression (CSD) is a slowly propagating (2–5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 76 publications
(108 reference statements)
4
43
0
2
Order By: Relevance
“…Indeed, a growing body of evidence convincingly demonstrates that microglia are recognized for acting as “busy bees” and maintain an expanding array of functions during both early brain development and adult homeostasis (Figure ). In particular, microglia can secrete a broad range of protective neurotrophic substances such as brain‐derived neurotrophic factor (BDNF), vascular endothelial growth factor, neuronal growth factor (NGF), insulin‐like growth factor‐1 (IGF‐1), platelet‐derived growth factors and transforming growth factor‐β (TGF‐β) (Butovsky et al, ; Parkhurst et al, ; Shibata & Suzuki, ; Wlodarczyk et al, ), thus ensuring appropriate neuronal network development and maintenance as well as enhancing memory and learning (Molteni & Rossetti, ; Parkhurst et al, ). There is a widespread consensus that microglia are also in active intimate contact with neighboring neuronal and non‐neuronal cells, thereby regulating neuronal proliferation, migration and differentiation and refining the neural circuits (Frost & Schafer, ; Mosser et al, ).…”
Section: Multi‐tasking Microglia: a Friend For Brain Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a growing body of evidence convincingly demonstrates that microglia are recognized for acting as “busy bees” and maintain an expanding array of functions during both early brain development and adult homeostasis (Figure ). In particular, microglia can secrete a broad range of protective neurotrophic substances such as brain‐derived neurotrophic factor (BDNF), vascular endothelial growth factor, neuronal growth factor (NGF), insulin‐like growth factor‐1 (IGF‐1), platelet‐derived growth factors and transforming growth factor‐β (TGF‐β) (Butovsky et al, ; Parkhurst et al, ; Shibata & Suzuki, ; Wlodarczyk et al, ), thus ensuring appropriate neuronal network development and maintenance as well as enhancing memory and learning (Molteni & Rossetti, ; Parkhurst et al, ). There is a widespread consensus that microglia are also in active intimate contact with neighboring neuronal and non‐neuronal cells, thereby regulating neuronal proliferation, migration and differentiation and refining the neural circuits (Frost & Schafer, ; Mosser et al, ).…”
Section: Multi‐tasking Microglia: a Friend For Brain Homeostasismentioning
confidence: 99%
“…Microglia are involved in regulating and shaping both excitatory and inhibitory synapses, such as γ‐aminobutyric acid‐expressing and glycinergic synapses (Cantaut‐Belarif et al, ; Um, ). Conversely, early evidence obtained from CX3CR1 gene‐deleted mice indicated that reduced numbers of microglial cells during brain development could impair the processes of synaptic pruning, resulting in a significantly higher density of dendritic spines and immature synapses (Paolicelli et al, ; Shibata & Suzuki, ). During adult neurogenesis, microglia actively contribute to regulate the dynamics, maintenance, and functions of synapses of adult‐born neurons (Reshef et al, ).…”
Section: Multi‐tasking Microglia: a Friend For Brain Homeostasismentioning
confidence: 99%
“…In fact, SD causes a considerable perturbation of the ionic environment in the brain, which may be readily detected by microglia and other nonneuronal cell types. It is conceivable that inflammation and microglial activation induced by PD‐related processes, long‐term l ‐dopa treatment, and repetitive inductions of striatal SD might trigger a vicious circle in the pathophysiology of basal ganglia and in LID induction and maintenance …”
Section: Discussionmentioning
confidence: 99%
“…Though the role of microglial activation in initiation of a single SD has been questioned (Shibata and Suzuki, 2017), our lab has shown that microglia are essential for induction of single SDs via synaptic activation (Pusic et al, 2014). Furthermore, there is evidence that the increased neural circuit excitatory drive necessary to elicit a single SD involves increased TNFα and reactive oxygen species that in turn play a role in SD initiation.…”
Section: Discussionmentioning
confidence: 99%